2020
DOI: 10.1145/3432189
|View full text |Cite
|
Sign up to set email alerts
|

VibroMap

Abstract: In spite of the great potential of on-body vibrotactile displays for a variety of applications, research lacks an understanding of the spacing between vibrotactile actuators. Through two experiments, we systematically investigate vibrotactile perception on the wrist, forearm, upper arm, back, torso, thigh, and leg, each in transverse and longitudinal body orientation. In the first experiment, we address the maximum distance between vibration motors that still preserves the ability to generate phantom sensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 68 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…The dimensions of the armband were determined by the distance between the actuators, which in turn were taken from [47]. It was ensured that the distance between the actuators in the longitudinal direction and in the circumferential direction were within a secure range for the PI.…”
Section: A Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions of the armband were determined by the distance between the actuators, which in turn were taken from [47]. It was ensured that the distance between the actuators in the longitudinal direction and in the circumferential direction were within a secure range for the PI.…”
Section: A Conceptmentioning
confidence: 99%
“…It was ensured that the distance between the actuators in the longitudinal direction and in the circumferential direction were within a secure range for the PI. The diagonal distance between the actuators was chosen to be slightly below the maximum two-point threshold on the forearm (as taken from [47]). We ensured sufficient space between the actuators to eliminate possible interference among each other.…”
Section: A Conceptmentioning
confidence: 99%
“…Relaying SRL feedback on the upper limbs, however, has an important drawback since it could interfere with natural proprioception of a body part that could be used concurrently (e.g., tri-manual manipulation or three-tools surgical assistance). For this reason, several authors preferred to place haptic stimulators on the lower back 122 , feet soles 123 , 124 or legs 84 , 125 , 126 , since previous results demonstrated that complex haptic stimulations can be successfully delivered to lower limbs as well 127 129 .…”
Section: Sensory Feedback and Srl Controlmentioning
confidence: 99%
“…Each actuator was positioned equidistantly from its neighbors, with 18 actuators on the front and back, 3 on each side of the waist, and 2 on each shoulder. Following VibroMap [29], the inter-actuator distances were about 8 cm.…”
Section: A Data Collection Proceduresmentioning
confidence: 99%